Influencia del cine en la Generación del 27 - Lobato, Flora (2008)
This article focuses on the influence cinema has had on literature, since as we have seen, the arrival of filmmakers led to a cultural revolution. The world of cinema was joined to other traditional arts, suchs as painting and literature, which man had already used to express his ideas and feelings. Cinema forms part of the new 20th century trends, influencing the poets of creating new imagery and metaphors which so greatly enhanced their work.